Spike discriminator within electrical records originated by groups of neurons. - García Moreira, Carlos; García Ruiz, Jaime; Marcelo, Maggi; Budelli, Rubén (Revista Mexicana de Ingenieria Biomedica, 1991)
The circuits of a pin discriminator have been classified in detail by overshoot and permanence with respect to the voltage levels chosen by the operator based on an oscilloscope multiplexed display. The device generates pulses for a computer through three lines of one of its ports. The test is illustrated with the records obtained from the cat’s olfactory bulb.